Childbearing intention and its associated factors: A systematic review - Mozhgan Hashemzadeh; Mohammad Shariati; Ali Mohammad Nazari; Afsaneh Keramat (Wiley, 2021)
Abstract Aim This study aimed to provide comprehensive information about the core determinants of fertility intentions. Design Systematic review. Methods Ovid, MEDLINE, EMBASE, PsycINFO, CINAHL, Web of Science, SCOPUS and GOOGLE SCHOLAR were searched for the relevant articles published from 1946-December 2017. We updated our records by searching three computerized databases (Ovid MEDLINE, SCOPUS and WOS) from 2018-January 2021. Results 53 studies included in the qualitative synthesis. The results of some studies indicated the impact of demographic factors, physical and psychological health, happiness and child desire. The most frequent variables in a couple's mesosystem were marital status, parity, partnership satisfaction and gender role attitude. The mesosystem of childbearing intention also included family and peers network. The EXEO system of the ECSM includes certain variables, such as job characteristics, urban residence, housing condition. The macrosystem comprises cultural and societal principles with broader influences on the couple's system.